Penerapan Media Pembelajaran berbasis Lingkungan pada Pembelajaran Fiqih di MI Tahfidz Cendikia Pekanbaru - Jailani, Ali Muddin (Lembaga Anotero Scientific Pekanbaru, 2024)
Fiqh learning has an important role in Islamic education, but conventional methods are often less effective in improving student understanding and engagement. This study aims to analyze the application of environment-based learning media in learning Fiqh at MI Tahfidz Cendikia Pekanbaru. The research method used is qualitative with an observation approach and interviews with teachers and students. The results showed that the use of the environment as a learning medium improved students' understanding of Fiqh concepts, increased learning motivation, and created a more contextual learning experience. However, there are obstacles in its application, such as limited resources and time. Environment-based learning can be an effective method to improve the quality of Fiqh learning. Therefore, support from the school and teachers in developing this method is needed to create a more interactive and meaningful learning process